A novel flow cytometric-based method to measure kinase inhibition in sputum from COPD subjects. Issue 1 (22nd June 2016) - Nicholson, G C; Holloway, R A; Leaker, B R; Kilty, I; Salganik, M; Tan, L; Barnes, P J; Donnelly, L E
Abstract : Introduction: Janus kinases (JAKs) regulate inflammatory gene expression through phosphorylation of signal transducer and activator of transcription (STAT) proteins. Expression of STAT proteins is increased in chronic obstructive pulmonary disease (COPD), and may be involved in driving chronic inflammation. Oral JAK inhibitors are effective as anti-inflammatory therapy but exhibit dose-limiting adverse effects. Development of inhaled compounds would be enhanced by robust biomarkers that directly reflect the anti-inflammatory and pharmacological activity in the lung. Methods: A novel flow cytometry assay was developed to measure STAT1 phosphorylation in sputum inflammatory cells. The standard sputum processing method was refined to improve sputum cell viability. The flow cytometric assay was used to assess the reproducibility of the measurement of STAT1 phosphorylation and the in vitro activity of a pan JAK-inhibitor on three separate visits in patients with COPD. Results: Upregulation of STAT1 phosphorylation was measured following in vitro IFNγ stimulation of sputum macrophages (stimulated/unstimulated ratio 1.57; p<0.00001). Upregulation was inhibited following in vitro preincubation with a pan JAK-inhibitor (inhibited+stimulated/unstimulated ratio 0.97). STAT1 phosphorylation activity could only be measured in macrophages. Conclusions: Sputum from patients with COPD can be used to reproducibly measure phospho-STAT expression in sputum macrophages. The flow cytometry-based method can be used to evaluate kinase inhibitors in vitro and subsequently in ex vivo studies. The assay is particularly useful for the assessment of inhaled compounds where whole blood assays may not be relevant.